Dampak Cyberbullying Bagi Masyarakat Indonesia dan Implementasi Peraturan Perundang-Undangan Negara dalam Melindungi Masyarakat Indonesia dari Cyberbullying - Istimeisyah, Dian; Hasnakusumah, Raisha Tiara; Marsanthy, Talitha Aqiella (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Cyberbullying is bullying via the internet using digital technology that often occurs among young people (teenagers) due to frequent access to things that are online. The purpose of this study is to determine the impact of cyberbullying and the implementation of laws and regulations in protecting Indonesian people from cyberbullying. This research uses a normative juridical research method with a statutory approach. The conclusion of this research is that cyberbullying has many impacts on society, especially teenagers and is regulated in Law No. 1 of 2024 concerning amendments to Law No. 19 of 2016 concerning Electronic Information and Transactions.